2020
DOI: 10.3390/ma13081820
|View full text |Cite
|
Sign up to set email alerts
|

A Review on Bubble Stability in Fresh Concrete: Mechanisms and Main Factors

Abstract: In order to improve the stability of air bubbles in fresh concrete, it is of great significance to have a better understanding of the mechanisms and main influencing factors of bubble stability. In the present review, the formation and collapse process of air bubbles in fresh concrete are essentially detailed; and the advances of major influencing factors of bubble stability are summarized. The results show that the surface tension of air–liquid interface exerts a huge impact on bubble stability by reducing su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(25 citation statements)
references
References 94 publications
0
23
0
2
Order By: Relevance
“…First, as well pointed by Sun et al [29], rubber modification reduces the viscosity and the flow resistance of the cement paste. Low plastic viscosity promotes the diffusion and the escape of air bubbles from the paste, preventing their retention in the hardening material [30]. Besides, rubber aggregates reduced water content in the cementitious mixes, maintaining proper fresh properties for printing (see Section 2.2).…”
Section: Figure 9 Rp-cement (A) and Rg-cement (B) Interfacial Adhesionmentioning
confidence: 99%
“…First, as well pointed by Sun et al [29], rubber modification reduces the viscosity and the flow resistance of the cement paste. Low plastic viscosity promotes the diffusion and the escape of air bubbles from the paste, preventing their retention in the hardening material [30]. Besides, rubber aggregates reduced water content in the cementitious mixes, maintaining proper fresh properties for printing (see Section 2.2).…”
Section: Figure 9 Rp-cement (A) and Rg-cement (B) Interfacial Adhesionmentioning
confidence: 99%
“…Nanoparticles are among the useful additives with promising influence in improving the performance properties of CBM and bituminous mixtures. Nanoparticles such as nano-SiO 2 and nano-TiO 2 are broadly used to enhance the strength and durability of CBMs [78,79]. Previous researches showed that nanoparticles in CBMs could react with Ca(OH) 2 crystals and generate more C-S-H gel, which occupies the void spaces and enhances the density of the interfacial transition zone [80][81][82].…”
Section: Use Of Additives In Ca Mortar Productionmentioning
confidence: 99%
“…However, in engineering practice, some researchers and engineers found that the air content of fresh concrete in the Qinghai-Tibet Plateau, which is known as the roof of the world, was lower than that in low elevation regions. In their opinion, this phenomenon is owing to the atmospheric pressure difference [ 6 , 7 ]. To prove this opinion, many works have been done, which mainly include the following: (i) shaking/agitation of AEA solutions in different air pressures [ 5 , 8 , 9 ]; (ii) concrete air content test at different elevations, corresponding to different atmospheric pressures [ 3 , 4 , 5 , 9 , 10 , 11 ]; and (iii) air content test of concrete mixed in different simulated air pressures [ 12 , 13 , 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%